Effect of Ozonated Avocado and High-Oleic Palm Oils on “Bolo Verde” Variety Squash - Ramírez Aura; Amariles Santiago; Hurtado-Salazar Alejandro; Ceballos-Aguirre Nelson (Horticulturae)
Ozonated oils have promise as biostimulants, positively affecting physiological processes that promote plant growth and biomass accumulation. However, additional research is required to clarify their mechanisms of action, optimize dosages, and define effective application strategies. This study aimed to evaluate the biostimulant effect of three concentrations of two oils, avocado (Persea maricana Mill cv Hass) (50, 100, and 200 meqO2 kg−1) and high-oleic palm (Elaeis guineensis Jacq.) (5, 10, and 20 meqO2 kg−1), on the “Bolo Verde” squash Cucurbita moschata. The experiment followed a completely randomized design with a three-factor factorial arrangement: Factor I—type of ozonated oil; Factor II—application concentration (low, medium, and high); Factor III—application method (drench or foliar). The trial consisted of 15 experimental units, each with 32 plants, totaling 480 plants. Data were analyzed using SAS software. A one-way ANOVA was performed, and means were compared using Tukey’s test p ≤ 0.05. The drench application of high-concentration ozonated avocado oil (200 meqO2 kg−1) produced the most favorable biostimulant response, significantly increasing plant height, leaf number, root length, root volume, and total dry weight. This was followed by the drench application of low-concentration ozonated high-oleic palm oil (5 meqO2 kg−1), which yielded the highest dry matter accumulation. For the net assimilation rate (NAR) and leaf area index (LAI), the drench application of ozonated avocado oil at a high concentration resulted in 4.29 g cm−2 day−1 NAR and 7957.99 LAI, while low-concentration high-oleic palm oil recorded 4.36 g cm−2 day−1 NAR and 7208.40 LAI. Both treatments showed statistically significant differences (p < 0.05) compared to the control 2.35 g cm−2 day−1 NAR and 6780.24 LAI, indicating improved photosynthetic efficiency and leaf expansion. Similar trends were observed for crop growth rate (CGR) and relative growth rate (RGR). The drench application of high-concentration ozonated avocado oil yielded a CGR of 6.77 × 10−4 g cm−2 day−1 and RGR 0.0441953 g g−1 day−1. Low-concentration high-oleic palm oil drench application resulted in the highest CGR of 7.35 × 10−4 g cm−2 day−1 and RGR 0.0454216 g g−1 day−1. These values were significantly higher than those of the control (CGR 4.14 × 10−4 g cm−2 day−1; RGR 0.0357569 g g−1 day−1). These results suggest that the drench application of ozonated oils not only enhances photosynthesis and leaf growth but also favors the incorporation and accumulation of biomass in “Bolo Verde” squash.